Rekonstruksi Konstitusi Terkait Konsep Wilayah Yang Utuh Dalam Negara Kesatuan Republik Indonesia - Athari Farhani (UIN Syarif Hidayatullah Jakarta, 2022)
Territory is an important attribute for a country, because it relates directly to aspects of sovereignty. In Indonesia, territory is regulated in Article 25A of the 1945 Constitution of the Republic of Indonesia and Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia which regulates state control over natural resources in the form of earth, water and the wealth contained therein. However, both of them do not reflect the concept of a complete territory or a 3-dimensional area, namely land, sea and air. Even though it is so important to regulate the territory and complete spatial planning, this is to provide certainty for the state in applying the boundaries of its territorial territory to maintain state sovereignty and protect all the potential of its natural resources.